Perception Analysis on COVID-19 Vaccination : An Online Cross-Sectional Study - Arora, Amit Kumar; Yadav, Sapna (Prabandhan: Indian Journal of Management, 2021)
Human society is vulnerable to COVID-19, and it has made daily life imbalanced in terms of the economy, mental health of people, and mortality. Indians are currently facing the brunt of the second wave of the COVID-19 pandemic. The Indian government is taking all the necessary actions to defeat COVID-19. More than 130 million Indians will need to be vaccinated soon to defeat COVID-19. At present, all people aged 18 years or above can register for the vaccination and book a slot as per their convenience. The current study aimed to examine people’s attitudes toward Corona vaccination and identify the motivating factors for registering and the reasons for not registering for the vaccination. The study was a primary cross-sectional study conducted in the Delhi-NCR region. The data collected through the structured questionnaire was analyzed through chi-square and descriptive statistics. The study found gender and age as the significant factors for registering for getting the vaccination. On the other hand, educational level and residential area were found to be the non-significant factors. The study determined the motivational factors and the reasons for registering or not registering for the vaccination.